Substitution of Soybean Dregs Flour and Addition of Guar Gum on the Chemical and Organoleptic Properties of Wet Noodles - Chasanah, Dwi Asmaul; Handarini, Kejora; Rahmiati, Retnani (Food Science and Technology Journal (Foodscitech), 2024)
Wet noodles substituted with soybean pulp flour produce noodle products that break easily and decreaseelasticity, so it is necessary to add guar gum to improve the quality of the wet noodles. This researchaims to determine the effect of interaction and determine the best combination between the proportionof soybean dregs flour and wheat flour with the addition of guar gum on the quality of wet noodlesincluding chemical and organoleptic properties. The research was carried out by making soy milk dregsflour first using a food dehydrator at a temperature of 60ºC for 4 hours, then making wet noodles with awheat flour substitution formulation using soy milk dregs flour and guar gum according to the treatment,then chemical and organoleptic tests were carried out. This research used a Completely RandomizedDesign (CRD) with a factorial pattern consisting of two factors. The first factor (A) is the proportion ofwheat flour and soybean dregs consisting of 3 levels, namely A1 (60%:40%), A2 (50%:50%), A3(40%:60%). The second factor (B) guar gum concentration consists of 2 levels, namely B1 (0.5%), B2(1%). The data obtained were analyzed using ANOVA. The research results showed that there was asignificant interaction between the proportion of soybean dregs flour and the addition of guar gumconcentration on water content, ash content, protein content, texture, color, aroma, taste, and there wasno significant interaction on fiber content. The treatment with the proportion of wheat flour and soybeandregs was 50%:50% and the addition of 0.5% guar gum was the selected treatment with parameters,namely texture = 4 (like), color = 4 (like), aroma = 4 (like), taste = 4 (like), water content = 62.52%, ashcontent = 0.94%, protein content = 19.34%, fiber content = 12.70%